2020
DOI: 10.1088/2053-1591/ab906a
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the effect of porosity on residual stress in 2024 aluminium alloy GTAW

Abstract: Simulations of the welding process for butt joints using finite element analysis (FEA) of the effect of porosity are presented. The metal used was aluminium alloy (grade 2024), and the filler material was alloy ER5356. The simulations were performed using the commercial software ANSYS, considering a double ellipsoid heat source, temperature-dependent material properties, material deposits, mechanical analysis, transient heat transfer, and defects (porosity). In this study, the FEA simulations were constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The formation of pores can be reduced by proper joint preparation, use of high purity shielding gas with lowdew-point and careful storage of the ller metal. However, the 5XXX series ller alloys, as used in this research, are particularly susceptible to surface oxide hydration, which promotes the porosity formation [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of pores can be reduced by proper joint preparation, use of high purity shielding gas with lowdew-point and careful storage of the ller metal. However, the 5XXX series ller alloys, as used in this research, are particularly susceptible to surface oxide hydration, which promotes the porosity formation [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Pores serve as stress risers that are brittle fractures and that increase the susceptibility to failure [ 39 ]. Several studies have shown that advanced tools can help detect faults or other defects that occur in the welding process such as ultrasonic non-destructive testing (NDT) techniques [ 30 ], X-ray CT methods [ 35 , 42 ], and radiographic testing (RT) [ 43 , 44 ]. The slow welding speeds and the welding in the flat position, or uphill in the vertical position, encourage the escape of pores [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To cross-validate the present zinc-induced porosity results in Al-Fe weld joints, results are compared with an independent approach based on x-ray computed tomography imaging. This technique allowed us to obtain a non-destructive, three-dimensional (3D) view of the weld and quantify any defects that may have occurred during the welding process [10]. The sample was placed on a rotating turntable between the x-ray source and detector, and x-rays were passed through the sample.…”
Section: X-ray Computer Tomography Imagingmentioning
confidence: 99%
“…Porosity defects can weaken the strength and integrity of the weld joint. Therefore it is essential to understand and quantify the porosity defects to optimize the GTAW processes [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation